6
$\begingroup$

Integrate

$$I=\int_{0}^{1}{\sqrt{1-x^4}\over 1+x^4}dx={\pi\over 4}$$

Substitution $x=\sqrt{\tan(u)}\rightarrow dx={\sec^2(u)\over 2\sqrt{\tan(u)}}du$

$x=1\rightarrow u={\pi\over 4}$

$x=0\rightarrow u=0$

$$I={1\over 2}\int_{0}^{{\pi\over 4}}{\sqrt{1-\tan^2(u)}\over 1+\tan^2(u)}\cdot {\sec^2(u)\over \sqrt{\tan(u)}}du$$

$$I={1\over 2}\int_{0}^{{\pi\over 4}}{\sqrt{1-\tan^2(u)\over \tan(u)}}du$$

$$I={1\over 2}\int_{0}^{{\pi\over 4}}{\sqrt{\cot(u)-\tan(u)}}du$$ Recall

$$\cot(u)-\tan(u)={\cos^2(u)-\sin^2(u)\over \sin(u)\cos(u)}=2\cot(2u)$$

Substitute back into I

$$I={1\over 2}\int_{0}^{{\pi\over 4}}{\sqrt{2\cot(2u)}}du$$

$$I={\sqrt2\over 2}\int_{0}^{{\pi\over 4}}{\sqrt{\cot(2u)}}du$$

Well I know that $$\int{\cos(2u)\over\sin(2u)}du={1\over 2}\ln(\sin(2u))+C$$ but

$$\int\sqrt{{\cos(2u)\over\sin(2u)}}du$$ I have not idea, so can anyone please give a hand? Thank.

$\endgroup$
  • $\begingroup$ Well here is a definite integral and other is an indefinite integral. That is the only difference I can see from it otherwise it is a duplicate. $\endgroup$ – gymbvghjkgkjkhgfkl Jun 4 '16 at 22:20
  • $\begingroup$ There is also a difference in the signs in front of $x^4$. $\endgroup$ – Hans Lundmark Jun 5 '16 at 6:15
  • $\begingroup$ You are right @HansLundmark how did I missed that! $\endgroup$ – gymbvghjkgkjkhgfkl Jun 5 '16 at 8:16
  • $\begingroup$ I have withdrawn my duplication comment, but I think it should be mentioned that I copied your integrand to the M.SE search engine and it "matched" to posts with $ \ \int \ \frac{\sqrt{1+x^4}}{1-x^4} \ dx \ $ . I should have checked back more carefully against your actual integral, but it also indicates that searches are not necessarily reliable here... $\endgroup$ – colormegone Jun 5 '16 at 22:16
4
$\begingroup$

You were so close! $$\begin{align}\int_0^{\frac{\pi}4}\sqrt{\cot2u}\,du&=\frac12\int_0^{\frac{\pi}2}\sqrt{\cot v}\,dv\tag{1}\\ &=\frac14\cdot2\int_0^{\frac{\pi}2}\cos^{1/2}v\sin^{-1/2}v\,dv\tag{2}\\ &=\frac14\text{B}\left(\frac34,\frac14\right)\tag{3}\\ &=\frac14\frac{\Gamma\left(\frac34\right)\Gamma\left(\frac14\right)}{\Gamma(1)}\tag{4}\\ &=\frac14\frac{\pi}{\sin\frac{\pi}4}\tag{5}\\ &=\frac{\pi}{2\sqrt2}\tag{6}\end{align}$$ EDIT: Some annotations:
$(1)$ Let $2u=v$
$(2)$ $\cot\theta=\frac{\cos\theta}{\sin\theta}$
$(3)$ Recognizing the trigonometric form of the Beta function
$(4)$ Using the relationship between the Beta and Gamma functions
$(5)$ The reflection formula for the Gamma function. We might equally have used the duplication formula $$\Gamma\left(\frac14\right)\Gamma\left(\frac34\right)=\sqrt{\pi}2^{1-2\left(\frac14\right)}\Gamma\left(2\left(\frac14\right)\right)=\sqrt{\pi}\sqrt2\sqrt{\pi}=\pi\sqrt2$$ $(6)$ Of course $\sin\frac{\pi}4=\frac1{\sqrt2}$. At this point we're home free and we can substitute the value of the integral into where you were stuck and arrive at $$\int_0^1\frac{\sqrt{1-x^4}}{1+x^4}dx=\frac{\sqrt2}2\frac{\pi}{2\sqrt2}=\frac{\pi}4$$

$\endgroup$
  • $\begingroup$ Why the downvote? I showed how to get from where he was stuck to the solution. Isn't that acceptable any more? $\endgroup$ – user5713492 Jun 5 '16 at 0:56
  • $\begingroup$ Yeah why the vote down! This is the point I am looking for. (+1) @user5713492. $\endgroup$ – gymbvghjkgkjkhgfkl Jun 5 '16 at 3:26
  • $\begingroup$ How did you get from 1st integral into the 2nd integral? $\endgroup$ – gymbvghjkgkjkhgfkl Jun 5 '16 at 3:32
  • $\begingroup$ I added some annotations in case my proof wasn't completely clear. Sometimes people try to disrupt the forum by downvoting randomly selected posts. $\endgroup$ – user5713492 Jun 5 '16 at 5:32
6
$\begingroup$

Let $y = x^2$ and $z = \sqrt{y^{-1} - y}$, we have $$\begin{align} \int_0^1 \frac{\sqrt{1-x^4}}{1+x^4}dx = & \int_0^1 \frac{x\sqrt{x^{-2} - x^2}}{x^2(x^{-2}+x^2)}dx = \int_0^1 \frac{\sqrt{x^{-2} - x^2}}{(x^{-2}+x^2)}\frac{dx}{x}\\ = & \frac12 \int_0^1 \frac{\sqrt{y^{-1}-y}}{y^{-1}+y}\frac{dy}{y} = -\frac12 \int_{y=0}^1 \frac{\sqrt{y^{-1}-y}}{y^{-1}+y}\frac{d(y^{-1} - y)}{y^{-1}+y}\\ = & \int_0^\infty \frac{z^2 dz}{z^4+4} = \int_0^\infty \frac{z^2 dz}{(z^2+2)^2 - (2z)^2} = \int_0^\infty \frac{z^2 dz}{(z^2-2z+2)(z^2+2z+2)}\\ = & \frac14 \int_0^\infty\left(\frac{z}{z^2-2z+2} - \frac{z}{z^2+2z+2}\right)dz\\ = & \frac14 \int_0^\infty \left[\frac12\log\left(\frac{z^2-2z+2}{z^2+2z+2}\right)' + \left(\frac{1}{z^2-2z+2} + \frac{1}{z^2+2z+2}\right)\right] dz \end{align} $$ The first piece contributes $\displaystyle\;\frac18 \left[\log\left(\frac{z^2-2z+2}{z^2+2z+2}\right)\right]_0^\infty\;$ which clearly vanishes.

For the second piece, substitute $z$ by $-z$ in its second term, we get:

$$\int_0^1 \frac{\sqrt{1-x^4}}{1+x^4}dx = \frac14 \int_{-\infty}^\infty\frac{dz}{z^2-2z+2} = \frac14 \int_{-\infty}^\infty\frac{dz}{(z-1)^2+1} = \frac{\pi}{4}$$

$\endgroup$
1
$\begingroup$

On the path of Achille Hui,

$\displaystyle J=\int_0^{\infty} \dfrac{x^2}{x^4+4}dx$

Perform the change of variable $y=\dfrac{x}{\sqrt{2}}$,

$\displaystyle J=\dfrac{\sqrt{2}}{2}\int_0^{\infty} \dfrac{x^2}{x^4+1}dx$

1)

Perform the change of variable $y=x^4$,

$\begin{align} J&=\dfrac{\sqrt{2}}{8}\int_0^{\infty} \dfrac{x^{-\tfrac{1}{4}}}{1+x}dx\\ &=\dfrac{\sqrt{2}}{8}\text{B}\left(\dfrac{3}{4},\dfrac{1}{4}\right)\\ &=\dfrac{\sqrt{2}}{8}\dfrac{\Gamma\left(\dfrac{3}{4}\right)\Gamma\left(\dfrac{1}{4}\right)}{\Gamma\left(1\right)}\\ &=\dfrac{\sqrt{2}}{8}\dfrac{\pi}{\sin\left(\tfrac{\pi}{4}\right)}\\ &=\dfrac{\sqrt{2}}{8}\dfrac{\pi}{\tfrac{\sqrt{2}}{2}}\\ &=\boxed{\dfrac{\pi}{4}} \end{align}$

2) alternatively

$\displaystyle J=\dfrac{\sqrt{2}}{4}\int_{-\infty}^{+\infty} \dfrac{x^2}{1+x^4}dx$

Perform the change of variable $y=\dfrac{1}{x}$,

$\displaystyle J=\dfrac{\sqrt{2}}{4}\int_{-\infty}^{+\infty} \dfrac{1}{1+x^4}dx$

therefore,

$\displaystyle 2J=\dfrac{\sqrt{2}}{4}\int_{-\infty}^{+\infty}\dfrac{1+\tfrac{1}{x^2}}{x^2+\tfrac{1}{x^2}}dx$

Observe that,

$x^2 +\dfrac{1}{x^2}=\left(x-\dfrac{1}{x}\right)^2+2$

Perform the change of variable $y=x-\dfrac{1}{x}$,

$\begin{align} 2J&=\dfrac{\sqrt{2}}{4}\int_{-\infty}^{+\infty} \dfrac{1}{x^2+2}dx\\ &=\dfrac{\sqrt{2}}{4}\left[\frac{\arctan\left(\frac{x}{\sqrt{2}}\right)}{\sqrt{2}}\right]_{-\infty}^{+\infty}\\ &=\dfrac{\pi}{2} \end{align}$

therefore,

$\boxed{J=\dfrac{\pi}{4}}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.